Impact of location and rank on the level of officer commitment towards community policing in Melaka - Yero, Aliyu; Othman, Jamilah; Sulaiman, Abdul Hadi; Abu Samah, Bahaman; Alby, Jeffrey Lawrence D'Silva (Universiti Putra Malaysia, 2012)
This study is interested in examining the commitment of Malaysian police towards community policing, specifically, the study is going to (a) find out whether commitment of police officers in Malaysia is affected by their rank and position in the hierarchy of the organization, and (b) to determine if there is any difference in commitment of officers based on district of duty. The survey method was utilized using a questionnaire adopted from previous studies on officer commitment, a total of 197 police officers responded from three districts of Alor Gajah, Jasin and Malacca Tengah in the state of Malacca. Officers who responded in this study were chosen through administrative recommendation. Findings reveal that majority of police officers in Malaysia have high commitment to community policing, results from the study also showed that there is a no significant difference in commitment level by rank of officers and district of duty.